The impact of the pandemic period on the occupational performance of students in the health area of the University of the State of Pará - Campus Belém (Research, Society and Development, 2022)
In times of COVID-19, social distancing is essential to prevent the spread of the virus and protect the population. However, it entails changes in people's routines. Among these are the university students, who needed to have modifications in their daily activities. The objective of this study was to identify losses in daily life and impairments in activities of students of the Center for Biological and Health Sciences of UEPA. This is a quantitative, descriptive and exploratory, cross-sectional approach, produced through a form with nine closed and multiple-choice questions, answered by the students. The majority of the research integrants was Occupational Therapy students. It was noted that most of the participants think that it is extremely important to have self-care, productivity and leisure; regarding the achievement of self-care and leisure, the majority of the participants tried but couldn’t do as expected, while no productivity was achieved by them. in addition, regarding satisfaction in achieving leisure, self-care and productivity, the results were mostly "not at all satisfied", "not satisfied" and "kind of satisfied", respectively. In conclusion, the social distancing results in problems on the activities performance of the participant students regarding self-care, productivity and leisure.